2018
DOI: 10.1021/acs.biochem.8b00381
|View full text |Cite
|
Sign up to set email alerts
|

Key Residues Affecting Transglycosylation Activity in Family 18 Chitinases: Insights into Donor and Acceptor Subsites

Abstract: Understanding features that determine transglycosylation (TG) activity in glycoside hydrolases is important because it would allow the construction of enzymes that can catalyze controlled synthesis of oligosaccharides. To increase TG activity in two family 18 chitinases, chitinase D from Serratia proteamaculans ( SpChiD) and chitinase A from Serratia marcescens ( SmChiA), we have mutated residues important for stabilizing the reaction intermediate and substrate binding in both donor and acceptor sites. To help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…This F396A mutation increased the K d value 2-fold and slightly reduced the processivity compared with WT (11,43). The slightly decreased K m was also observed when Phe-396 was mutated to Trp with D313N (44,45). Taken together, F232W/F396W mutation in SmChiA would be better in guiding the chitin chain, whereby the binding affinity was increased and the degree of processivity was improved as a result of the larger aromatic surface area of Trp compared with Phe.…”
Section: Mechanism Of Smchia High-catalytic-activity Mutantmentioning
confidence: 79%
“…This F396A mutation increased the K d value 2-fold and slightly reduced the processivity compared with WT (11,43). The slightly decreased K m was also observed when Phe-396 was mutated to Trp with D313N (44,45). Taken together, F232W/F396W mutation in SmChiA would be better in guiding the chitin chain, whereby the binding affinity was increased and the degree of processivity was improved as a result of the larger aromatic surface area of Trp compared with Phe.…”
Section: Mechanism Of Smchia High-catalytic-activity Mutantmentioning
confidence: 79%
“…Previous results reported that the mutation F396A, the equivalent residue in SmChitA, had little impact on hydrolysis of crystalline chitin and only moderate impact on processive ability on chitosan [15] , which was explained as this Phe having little role in ligand binding by calculating the free energy through experimental and MD simulation techniques [42] . However, the replacement of Phe by Trp increases markedly its transglycosilation ability [18] revealing a role in acceptor substrate binding. Nevertheless, it is worth noting that, while loop β6-α6 of the SmChitA is quite conserved with Chit42, the adjacent CID domain is the most variable region and, in particular, SmChitA presents longer β7aβ7b and β7b-β7c loops ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although this reaction is secondary to the hydrolytic activity, the balance can be kinetically controlled and has been proved to be modulated by mutagenesis of key residues at the catalytic site, and also by removal of some aromatics at the active site groove of chitinases from Serratia [17] . Thus, mutations leading to decreased rate of hydrolysis and enhanced sugar acceptor-binding access may result in an increased level of TG products [18] . Therefore, a full understanding of the catalytic mechanism and depiction of subsites affinities is required to fully exploit the synthetic use of chitinases.…”
Section: Introductionmentioning
confidence: 99%
“…Three main approaches have been identified to create TGs starting from rGHs [16]. The first involves the modification of substrate interactions in the donor subsite(s), leading to increased transition state (TS) energy barriers [26,27]. The aim is to reduce the efficiency of watermediated deglycosylation, thus favouring transglycosylation, although overall catalytic activity is also affected.…”
Section: Introductionmentioning
confidence: 99%
“…transglycosylation). This is often achieved by introducing hydrophobic amino acid side chains at the acceptor site(s), which form favourable interactions with incoming glycoside acceptors and repel water molecules [26,28,29]. When combined with donor subsite engineering, the introduction of favourable acceptor site interactions can partially compensate for the overall reduction in efficiency due to the poor formation of the glycosyl-enzyme intermediate [30].…”
Section: Introductionmentioning
confidence: 99%